2020
DOI: 10.3390/ma13122880
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning and Conditioning of Contaminated Core Build-Up Material before Adhesive Bonding

Abstract: The objective of this study was to evaluate the effects of different cleaning and conditioning procedures after contamination on the tensile bond strength (TBS) of a luting resin to a core build-up composite resin. Specimens (n = 384) made of a core build-up material were stored for 3 weeks in 37 °C water. Half of the specimens were contaminated with saliva and a disclosing silicone and then cleaned either using phosphoric acid, a pumice suspension, air-abrasion with alumina or polishing powder. Surface condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…For bonding of resin core foundation in dental practice, a more chemical adhesive should be used to ensure proper fit of the prosthesis during the luting procedure. Contamination of the resin core foundation surface inhibits the wetting of the adhesive and, given the surface characteristics of the substrate, reduces the probability of chemical interaction 8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For bonding of resin core foundation in dental practice, a more chemical adhesive should be used to ensure proper fit of the prosthesis during the luting procedure. Contamination of the resin core foundation surface inhibits the wetting of the adhesive and, given the surface characteristics of the substrate, reduces the probability of chemical interaction 8) .…”
Section: Discussionmentioning
confidence: 99%
“…One is that the glycoproteins in saliva adhere to adherent surfaces by a chemical bonding process, rendering the adherent surface unsuitable for adhesion by resin luting cement 7) . A previous study suggested that cleaning the salivacontaminated core foundation material surfaces with alumina-particle air abrasion results in statistically significantly higher bond strength than cleaning with phosphoric acid etching 8) . Various ways can be used to clean the adherent surfaces from contamination.…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, multiple clinical trials have indicated no significant differences in survival and success rates were found between teeth with existing composite fillings and those without [39,44,58]. In addition, several in vitro studies suggested that employing appropriate surface treatment methods for polymerized composites, including airborneparticle abrasion with alumina particles and the application of silane, can enhance the bond strength to resin luting agents [59,60].…”
Section: Dentin Exposure Of Abutment Teethmentioning
confidence: 99%
“…Given the similarity of composition between the resin cement and resin composite of the prosthetic core, it is possible to predict an excellent bond strength at this interface, although the operative steps should be considered as possible modi ers of the adhesive surface of the core in uencing the bond between these two materials [11]. Even so, the weak link of adhesive cementation of the bilayer crown with metallic infrastructure is still the interface between resin cement and metallic alloy.…”
Section: Introductionmentioning
confidence: 99%